Kinematic and Kinetic Analysis of Repeated and Static Elevé in Adolescent Female Dance Students. Issue 1 (March 2018) - Abraham, Amit; Dunsky, Ayelet; Hackney, Madeleine E.; Dickstein, Ruth
Elevé is a fundamental dance movement practiced routinely by dance students and serving as an integral component of screening in dance. It consists of ankle plantar flexion (PF) movement and is considered to be a frequent cause of foot and ankle injuries among dancers, with adolescent female dance students being at greatest risk for such injuries. Therefore, gaining additional knowledge regarding elevé functional range of motion (ROM) and inter-leg weightbearing distribution (WBD) properties among adolescent dance students is warranted for pedagogic, screening, injury prevention, and rehabilitation purposes. The aims of this study were three-fold: 1. to report and compare dance-specific, functional kinematic (ankle PF maximum angle and ankle PF ROM), kinetic (inter-leg WBD), and self-reported level of difficulty (balance, muscular force, and concentration) properties of repeated and static elevé among adolescent female dance students; 2. to look for correlations between elevé properties and participants' demographics (age, height, weight, dance experience, and leg dominance); and 3. to describe the relationships between the two kinematic properties in both elevé tasks. Twenty-three adolescent female dance students (mean age 13.57 ± 0.50 years) were measured while performing two elevé tasks: 10 repetitions ("repeated elevé task") and 10 consecutive seconds hold ("static elevé task"). Data regarding ankle motion and WBD were collected and analyzed using three-dimensional motion capture and two force plates. The data gained from this study expand our current understanding of elevé dance movement and may contribute to clinical relevancy and applicability of screening procedures being conducted in pre-professional dance settings. This may help to identify adolescent dance students with the potential to undertake a career in professional dance as well as to investigate the parameters associated with risk of ankle injuries in this population.